PENGGUNAAN GAYA BAHASA PENEGASAN PADA NASKAH PIDATO KENEGARAAN PRESIDEN RI DALAM RANGKA HARI PROKLAMASI KEMERDEKAAN RI YANG KE-70 - Nur Aini Syah (Universitas Sebelas Maret, 2019)
The purpose of this study to find a variety confirmation language style, and the influence of stilistika dominant aspects in his President official speech. The study was descriptive qualitative research. The data in this study is a lingual unit in the form of words, phrases, or clauses that contains stilistika study. The data sources in this study is official speech of the President of the Proclamation of 70th Independence. The data acquisition techniques is see and note. The results of this research is there are 10 stylistic confirmation style, apositif, redundancy, repetition, alliteration, paralisme, tautalogi, sigmatisme, climax, eksklamasio and enumerasio. The dominant confirmation language is enumerasio with 27.7%. The Influence of President language style is to emphasize about the things that are encouraging and less encouraging, and about the important things